KEKERASAN SEKSUAL PADA REMAJA DALAM PERSPEKTIF PERKEMBANGAN PSIKOSOSIAL ERIK ERIKSON DAN IMPLIKASINYA TERHADAP LAYANAN BIMBINGAN KONSELING - Ramadhani, Hikmah; Lu’lu ‘aabidah; Neza Dwi Nasyfa; Rofiq Raihan Nabih; Rahmi Anekasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Sexual violence among adolescents remains a serious issue occurring both directly and through digital media. This study aims to examine adolescent sexual violence from Erik Erikson’s psychosocial development perspective and identify its implications for guidance and counseling services. The research employed a qualitative literature review method by analyzing journals, books, articles, and previous studies related to sexual violence, psychosocial development, and counseling. The findings show that adolescents are vulnerable to sexual violence due to identity crises, emotional instability, peer influence, and extensive social media use. Such experiences can hinder healthy identity formation and lead to trauma, anxiety, low self-confidence, and difficulties in social relationships. Guidance and counseling services play an important role in prevention and intervention through information services, counseling, victim assistance, and sexuality education. Therefore, collaboration among schools, families, and counselors is needed to create a safe environment and support adolescents’ psychosocial development.